PEMBUATAN ECOENZIM BERBASIS LIMBAH ORGANIK UNTUK MENDUKUNG PENGUATAN PROFIL PELAJAR PANCASILA (P5) DI SMA NEGERI WOLWAL - Desiana Maimakal; Salomi Mallau; Julinda Maata; Leri Lepangkari; Marsalina Langfan; Daud Lahlau; Martasiana Karbeka; Herianus Manimoy; Hul Martha Adang (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The Pancasila Student Profile Strengthening Program (P5) is an initiative designed to shape students' character holistically, in accordance with the noble values ​​of Pancasila, which are the foundation of national and state life. One concrete step in implementing this program is through community service activities carried out by students of the Chemistry Study Program, Tribuana Kalabahi University, at Wolwal High School. This activity not only aims to provide technical knowledge regarding ecoenzyme production, but also plays a role in strengthening the P5 dimensions which include mutual cooperation, independence, critical thinking, creativity, and global diversity. In this activity, Tribuana Kalabahi University students integrate the chemistry theory they have learned with the direct practice of making ecoenzymes from organic waste. The creation of ecoenzymes, which is an environmentally friendly solution in waste management, is an effective medium for instilling students' understanding of the importance of environmental awareness and the practical application of chemical concepts. Through this activity, students are not only involved in the technical process of ecoenzyme production but are also empowered to think critically about innovative, creative, and sustainability-based environmental solutions. They are trained to work collaboratively in groups, reflecting the spirit of mutual cooperation, while simultaneously developing independence in carrying out practical tasks. Furthermore, this activity also provides a space for students to appreciate diversity, strengthen open attitudes, and deepen their sense of responsibility towards environmental issues, which aligns with the values ​​of global diversity in P5.